A TRANSLATION ANALYSIS OF JAVANESE ANCIENT CULTURE-BOUND TERMS IN THE NOVEL ENTITLED AROK OF JAVA BYPRAMOEDYA ANANTA TOER - Poppi Furi Nopianti, - (2010)
This present study is conducted under the title A Translation Analysis of Javanese Ancient Culture-bound Terms in the Novel Entitled Arok of Java by Pramoedya Ananta Toer. The aims of the study are to investigate the cultural categories of the Javanese ancient culture-bound terms found in the novel Arok of Java and to figure out the translation procedures applied in translating the Javanese ancient culture-bound terms into English and whether the procedures applied are appropriate or not. This study employs a descriptive design with a qualitative approach in analyzing the obtained data which are the culture-bound terms discovered in the novel. By using a qualitative approach, this study does not make or proof hypotheses, it just established data collection, conducting the observation carried out from the cases then build a knowledge which is understandable and applicable in translation theory. The results of the study indicate that there are 4 kinds of cultural categories discovered in the novel. These kinds of cultural categories are categorized based on Newmark (1988), see also Nida (1975). Those are: Ecology: Flora (2.8%), Fauna (1.6%), Material culture: Artifact (13.2%), Houses and towns (3.2%), Clothes (2.8%), Food (2.4%), Transportation (0.4%). Social culture: Work (6.4%), Leisure (0.8%). Organization: Religious (48%), Political (6.4%), Social (5.2%), Historical terms (4%), Artistic terms (2.8%). Religious term is the cultural category that is frequently discovered in the novel. Furthermore, eleven procedures are applied by translator in translating Javanese ancient culture-bound terms. The translation procedures are offered by Newmark (1988), Catford (1965), Vinay and Darbelnet (1995), Delisle (1999), Graedler (2000) and Harvey (2003). The data analysis shows that the eleven translation procedures are literal (6.8%), transference (17.6%), naturalization (2.8%), cultural equivalent (19.6%), descriptive equivalent (9.6%), synonymy (0.8%), transpositions (7.6%), couplets (24.8%), translation label (0.4%), compensation (1.2%), and notes (8.8%). Couplets procedure is the most frequent procedure used by the translator in translating Javanese ancient culture-bound terms. Most of the translations are accurate and acceptable since it fulfills the criteria of good translation: accuracy, clarity, and naturalness (Barnwell, 1986: 23) and it also fulfills the equivalence in translation proposed by Nida (1975:159), Koller cited in Munday (2001: 47), Baker (1992) and Skopos theory (Vermeer cited in Routledge 2000: 229). The research results provide some valuable information for translators, particularly translation of culture-bound terms.